Immunotherapy in renal cell carcinoma: latest evidence and clinical implications - Matteo Santoni; Francesco Massari; Vincenzo Di Nunno; Alessandro Conti; Alessia Cimadamore; Marina Scarpelli; Rodolfo Montironi; Liang Cheng; Nicola Battelli; Antonio Lopez-Beltran (BioExcel Publishing Ltd, 2018)
Advances in understanding the mechanisms of tumour-induced immunosuppression have led to the development of immune-checkpoint inhibitors in cancer patients, including those with renal cell carcinoma (RCC). The optimal combination between immunotherapy and targeted agents (as well as the possible favourable sequential therapy of these two classes of drugs) remains an open question at this moment. Several trials are currently underway to assess the combination of anti-programmed-death 1 (PD-1) or anti-PD-ligand(L)1 agents with other immunotherapies or with anti-vascular endothelial growth factor receptor (VEGFR) tyrosine kinase inhibitors (TKIs). In this editorial, we described the results of the most recent clinical trials on the use of immunotherapies in RCC and the emerging data on the research for reliable biomarkers of tumour response in this setting. In addition, we have focused on the role of the gut microbiome and tumour microenvironment in the development of future therapeutic strategies for RCC patients.